Downregulation of 5‐hydroxymethylcytosine is an early event in pancreatic tumorigenesis. Issue 3 (21st May 2021) - Fujikura, Kohei; Alruwaii, Zainab I; Haffner, Michael C; Trujillo, Maria A; Roberts, Nicholas J; Hong, Seung‐Mo; Macgregor‐Das, Anne; Goggins, Michael G; Roy, Sujayita; Meeker, Alan K; Ding, Ding; Wright, Michael; et al.
Abstract: Epigenetic alterations are increasingly recognized as important contributors to the development and progression of pancreatic ductal adenocarcinoma. 5‐hydroxymethylcytosine (5hmC) is an epigenetic DNA mark generated through the ten‐eleven translocation (TET) enzyme‐mediated pathway and is closely linked to gene activation. However, the timing of alterations in epigenetic regulation in the progression of pancreatic neoplasia is not well understood. In this study, we hypothesized that aberrant expression of ten‐eleven translocation methylcytosine dioxygenase 1 (TET1) and subsequent global 5hmC alteration are linked to early tumorigenesis in the pancreas. Therefore, we evaluated alterations of 5hmC and TET1 levels using immunohistochemistry in pancreatic neoplasms ( n = 380) and normal ducts ( n = 118). The study cohort included representation of the full spectrum of precancerous lesions from low‐ and high‐grade pancreatic intraepithelial neoplasia ( n = 95), intraductal papillary mucinous neoplasms (all subtypes, n = 129), intraductal oncocytic papillary neoplasms ( n = 12), and mucinous cystic neoplasms ( n = 144). 5hmC and TET1 were significantly downregulated in all types of precancerous lesion and associated invasive pancreatic ductal adenocarcinomas compared with normal ductal epithelium (all p < 0.001), and expression of 5hmC positively correlated with expression of TET1. Importantly, downregulation of both 5hmC and TET1 was observed in most low‐grade precancerous lesions. There were no clear associations between 5hmC levels and clinicopathological factors, thereby suggesting a common epigenetic abnormality across precancerous lesions. We conclude that downregulation of 5hmC and TET1 is an early event in pancreatic tumorigenesis. © 2021 The Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.